2018
DOI: 10.2152/jmi.65.116
|View full text |Cite
|
Sign up to set email alerts
|

The ratio of contrast medium volume to estimated glomerular filtration rate as a predictor of contrast‐induced nephropathy after endovascular aortic repair

Abstract: The CV/eGFR ratio was a useful predictor of contrast medium-induced nephropathy after EVAR. It is possible that the score can be used in patients when managing the EVAR techniques and contrast medium volume. J. Med. Invest. 65:116-121, February, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 23 publications
0
9
1
Order By: Relevance
“…Several pre-operative risk factors of CI-AKI have been identified including the age of the patients and baseline kidney function. [14][15][16][17]44 Although they are well-established risk factors of CI-AKI, we did not observe a significant difference regarding these two factors in our cohort between patients who developed CI-AKI and those who did not. However, it is possible that the distribution of age in our cohort may not have allowed to identify a significant difference.…”
Section: Discussioncontrasting
confidence: 62%
See 3 more Smart Citations
“…Several pre-operative risk factors of CI-AKI have been identified including the age of the patients and baseline kidney function. [14][15][16][17]44 Although they are well-established risk factors of CI-AKI, we did not observe a significant difference regarding these two factors in our cohort between patients who developed CI-AKI and those who did not. However, it is possible that the distribution of age in our cohort may not have allowed to identify a significant difference.…”
Section: Discussioncontrasting
confidence: 62%
“…12,13 Previous studies reported an incidence of CI-AKI in patients undergoing EVAR between 6.9 and 28%. 12,[14][15][16][17][18][19][20] In the present cohort of 102 patients, we report for the first time, the incidence of CI-AKI specifically in patients who underwent ch-EVAR, with a rate of 13.7%, which is within the low range compared with other EVAR procedures. In our center, we applied an "as low as reasonably achievable" approach and the median of CM used was low (85 mL), which could partly explain a relatively low rate of incidence of CI-AKI.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…31 Furthermore, the ratio of contrast media volume to GFR was demonstrated to predict CIN after endovascular aortic repair. 32 A relationship has also been established between increased baseline proteinuria and CIN in patients undergoing renal artery stent placement. 33 C-reactive protein was found to be an independent predictor of CIN after coronary angiography.…”
Section: Discussionmentioning
confidence: 99%